Pendampingan Produksi Konten Berita pada Pemberitaan Media Sosial Metro Today - Wahyu1, Ana Sofiana; Armilia, Elfira; Sabila, Amelia Hidayatus; Restu Ramadhan Pinem, M. Ervin; Shofiya Asy`ari, Nur Aini (Universitas Pahlawan Tuanku Tambusai, 2025)
The lack of public interest and engagement with news content is a problem for local media in Sidoarjo. One local news portal, Metro Today, needs help to improve the quality and appeal of its social media content. The goal of this community service initiative is to help Metro Today create material that meets the needs of its readers. Audience needs analysis, identification of local issues, posting scheduling, assistance in text, image, and video creation, interactive strategies through audience engagement, and content performance evaluation are some of the techniques used. Although viewership remains an issue, the results of these activities show an increase in the diversity and quality of material, community interaction through active comments, and some content achieving high levels of engagement. The capabilities of the Metro Today team have improved, and a more active local information ecosystem has been strengthened as a result of these actions.